Duelo y aceptación ante la perdida de una extremidad de un adulto de 55 años - Fuentes Chompol, Ulises Javier (2021)
This clinical case focused on the study of bereavement and acceptance loss of a limb in a 55-year-old adult. Which was developed under the use of methodology and psychometric tests, being tools that allowed the collection of data for the analysis and elaboration of a diagnosis. Based on THED-10 criteria, the following diagnosis was identified: F32.2 severe depressive episode without psychotic symptoms, from the loss of its limb. Grief and acceptance is a process to cope with the situation in a better way that does not cause serious problems in the future, so this project deals with the acceptance of the loss of a member and the natural stages that an individual pass. Depression occurs with bad thoughts regarding life, the process of therapy in the patient is fundamental to improve their thinking and situation, in which positive results are achieved.